AN ANALYSIS OF ACEH TOMB STONE DISTRIBUTION IN DEAH GLUMPANG VILLAGE, MEURAXA SUB-DISTRICT - Teungku Ivaluddin; Nasrullah (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
One of the parts of Banda Aceh's city that is near the seaside is Deah Glumpang village. This region was a part of Sagoe XXV during the reign of the Aceh Darussalam kingdom and had a separate political structure. Gampong Deah Glumpang is a fascinating region to explore since it has a high density of Aceh tombstones. Gampong Deah Glumpang is home to a variety of and quite densely decorated Aceh tombstones. The purpose of the research done in the village of Deah Glumpang is to describe the circumstances, identify the gravestones, and assess their distribution. The research method used is descriptive analysis with an inductive approach. Data collection techniques include assessments, surface surveys, interviews, and literature studies. After all these activities have been carried out, the data will be described and analyzed, which includes morphological, technological, stylistic, and contextual analysis. The results of the study found that the distribution of Acehnese tombstones in Gampong Deah Glumpang was spread over 11 points of the Aceh tombstone group. In total, there are 173 Aceh tombstones, 35 that have not been identified due to severe damage, and the remaining 131 that are identified by the shape of winged slabs, wingless slabs, winged square beams, octagonal inverted cones, and cylindrical inverted cones. According to Othman Yatim's periodization and comparison with the distribution of Acehnese tombstones in other areas in Banda Aceh and Aceh Besar, it was revealed that the distribution of Acehnese tombstones in Gampong Deah Glumpang originates from the XV-XIX century. Other findings are ceramics and the remains of old structures, so it is strongly suspected that apart from being an ancient burial area, it was also used as an ancient settlement around the burial site.